ANALISIS KEMAMPUAN PEMAHAMAN KONSEP SISWA PADA MATERI SPLDV DITINJAU DARI KEPRIBADIAN EKSTROVERT DAN INTROVERT DI SMPN 7 PALU - Rizal, Muh.; Idris, Mustamin; Nurhayadi, Nurhayadi; Annisa, Marsiana Dwi (Aksioma, 2025)
This study aims to describe the concept understanding ability of students on SPLDV material in terms of extroverted and introverted personalities at SMPN 7 Palu. The type of qualitative research is descriptive. The subjects of this study were students of class VIII D SMPN 7 Palu consisting of 20 students. However, in this study the subjects that researchers used were one student with introverted personality and one student with extroverted personality. Data collection techniques used personality questionnaires, written tests and interviews. The results of this study indicate that (1) Introverted students restate a concept by restating equation 1 and equation 2 obtained from the problem into another form, namely the SPLDV form correctly and tend to imitate what is in the problem without using their own language. Meanwhile, extroverted students restate a concept by restating the equations obtained from the problem into another form, namely the SPLDV form in their own language, not influenced by information from the problem and more likely to use their own language. (2) Introverted students provide examples of SPLDV and those that are not SPLDV based on examples of SPLDV obtained from the problem. While extroverted students provide examples that include SPLDV by looking at the SPLDV example that SE gets in the problem, but SE is unable to provide examples that do not include SPLDV because there are no examples, this means that SE can provide examples if you see an existing example. (3) Introverted students present concepts in various forms of mathematical representation in a structured manner, the steps are clear by writing in full what is known from the problem and then presenting it in the form of a mathematical model. Meanwhile, extroverted students present concepts in various forms of mathematical representation on the system of linear equations of two variables by directly presenting it in the form of a mathematical model without clear and unstructured steps by not writing what is known from the problem and directly presenting it in the form of a mathematical model. (4) Introverted students can develop necessary or sufficient conditions for a concept by writing and developing the exact conditions of one SPLDV solution and being able to determine the value of a correctly along with a clear and complete solution. Meanwhile, extroverted students develop the necessary or sufficient condition of a concept and determine the value of a by answering carelessly without doing the solution. (5) Introverted students use, utilize and select certain procedures or operations and apply concepts by determining what methods should be used in solving SPLDV problems in a structured manner, the steps are clear and the final results obtained are correct. While extroverted student subjects use, utilize, and select certain procedures or operations and apply concepts to SPLDV material with incorrect final results.